(untitled) (Journal of Libya for geographical studies, 2023)
The urban hinterland of the city of Shahat is witnessing a clear spread of the phenomenon of second homes in an unprecedented manner. This spatial spread has three characteristics: speed, continuity and randomness. Despite this, this phenomenon did not receive a study examining its aspects from a spatial perspective, so this study is concerned with tracking the growth of the phenomenon of second homes, and analysing its distribution and density, the degree of spacing and the factors for choosing the sites of the second homes, the rate of spread and their distance from the main urban center in the province of the city of Shahat. In order to reach the aim of the study, the second homes in the region of the city of Shahat were identified through the satellite imagery of Sentinel 2A, 2022, as well as reliance on the field study of a sample of second homeowners, in the region of the study, through 120 questionnaires , which constituted 28% of the total number of second homes in the region of the city of Shahat in 2022. For data analysis, the descriptive method was based. The study has reached many results, the most important of which is the concentration of most of the second homes around the city of Shahat as the main urban center in the study region, especially in the area between it and the city of Sousse, near the city of Shahat in the south and the sea beach in the north. The vicinity of the city of Shahat to reach 91% of the second homes in the study area with a distance of no more than ten kilometers, and this will make these homes offer to turn into permanent housing when the random urban growth of the city of Shahat reaches these second homes in the future.